Transferable Plasmids of Salmonella enterica Associated With Antibiotic Resistance Genes - McMillan, Elizabeth A.; Jackson, Charlene R.; Frye, Jonathan G. (Frontiers in Microbiology, 2020)
Salmonella enterica is a common foodborne illness in the United States and globally. An increasing number of Salmonella infections are resistant to antibiotics and many of the genes responsible for those resistances are carried by plasmids. Plasmids are important mediators of horizontal gene exchange, which could potentially increase the spread of antibiotic resistance genes. Twenty-eight different incompatibility groups of plasmids have been described in Enterobacteriaceae. Incompatibility groups differ in their accessory gene content, replication mechanisms, and their associations with Salmonella serotypes and animal sources. Plasmids also differ in their ability to conjugate or be mobilized, essential genes, and conditions required for transfer. It is important to understand the differences in gene content and transfer mechanisms to accurately determine the impact of plasmids on the dissemination and persistence of antibiotic resistance genes. This review will cover the most common plasmid incompatibility groups associated with Salmonella enterica with a focus on the transfer mechanisms and associated antibiotic resistance genes.